THE BEST MODEL AND VARIABLES AFFECTING HOUSING VALUES OF BIG CITIES IN INDONESIA - Anak Agung Gde Satia Utama (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of this study is to provide the best model and provide information on what factors affect the selling price of a house in two major cities in Indonesia, namely Surabaya and Denpasar. This study uses web-based survey data on one of the largest home sales sites in Indonesia. The data obtained were 110 houses and processed using Minitab software. Data analysis uses regression. The results obtained indicate that there are differences in factors that affect the selling price of houses in the two cities. The electric power factor (kilowatt hour) and land area (LSF) are both factors that affect housing prices in both cities. The contribution of this research can be additional information for consumers, developers, or property investors in the activity of demand transactions and offers for home sales.